(untitled) - Frankfort-Nachmias, Chava (New York, 1992)
The book introduces all the key qualitative and quantitative research methodologies and methods and seeks to draw readers into a community of researchers engaged in reflection on the research process. Included are narrative accounts of carrying out a research study that explore the way in which the research design and methods are shaped by the methodology, discussing problematic issues, and reflecting on the way in which knowledge and understanding develop. Aimed at researchers and postgraduate students, it will also be invaluable for students at masters level.
Keywords: Social sciences,Social sciences,Khoa học xã hội,Khoa học xã hội; Methodology,Research,Phương pháp luận,Nghiên cứu